Impact of Financial Ratios on Stock Prices - Sufiati; Dahniyar Daud; Rizky Aprilio Sakti (www.amertainstitute.com, 2025)
Stock prices are very important for investors because they can help investors provide an overview of the company's performance and the value of the company itself. The higher the stock price of a company, the higher the value of the company, and vice versa. This study aims to analyze stock prices used to explain the influence of independent variables, namely Profitability, Liquidity, and Solvency (Case Study on Banking Companies Listed on the Indonesia Stock Exchange for the 2021-2023 Period). Data collection in this study uses secondary data obtained from financial reports published and issued by the Indonesia Stock Exchange using Purposive Sampling Techniques . The population in this study is the Banking Sector Companies listed on the Indonesia Stock Exchange during the 2021-2023 period amounting to 45 companies. The research sample used was 99 sample data. The results of the variable data in this study have been tested with classical assumption tests in the form of normality, multicollinearity, and heteroscedasticity assumption tests. This data analysis method uses multiple linear regression techniques. The results of this study indicate that the Profitability variable has a significant positive effect on Stock Prices, Liquidity does not have a significant effect on Stock Prices, and Solvency has a significant negative effect on Stock Price Compliance.